Stress assessment using salivary cortisol in collegiate athlete - by focusing on the cortisol awakening response - Kadooka, S.; Hirata, K.; Sugo, T. (Japanese Journal of Physical Fitness and Sports Medicine, 2013)
Past studies have suggested that the cortisol awakening response (CAR) is a robust index for assessing daily stress. The present study examined the stability of CAR in individuals and the relationship between CAR and moods states and the influence of gender on CAR. CAR was measured in two successive days. Participants were student athletes (men=36, women=12) in a university athletic club that participated in club practice over five days a week. They were instructed to collect saliva just after and 30 minutes following awakening. The Moods was measured using the short form of the Profile of Moods States (POMS-S). The results indicated high stability of CAR values for the two successive days. Furthermore, there was a relationship between CAR and negative moods. Moreover, women showed significantly lager increases of the early morning free cortisol levels after awakening compared to men.